Формування професійної ідентичності майбутніх молодших спеціалістів сестринської справи - Саблук, Анатолій; Біда, Олена (Східноєвропейський національний університет імені Лесі Українки, 2018)
Актуальним стає пошук ефективних способів забезпечення професійного зростання майбутніх молодших спеціалістів сестринської справи в освітньому середовищі медичного коледжу. З’ясовано, що виокремлюють три типи ідентичності: психофізіологічну; соціальну; особистісну. Професійна ідентичність є обов’язковою складовою професіоналізму майбутнього фахівця й однією з умов його формування. У професійній ідентичності виокремлюють два аспекти: 1) усвідомлення себе представником певної професії та професійної спільноти; 2) розглядають її як результат процесів професійного самовизначення, персоналізації й самоорганізації. Основний вплив на формування професійної ідентичності мають такі виділені групи чинників: об’єктивні, чи зовнішні, чинники, пов’язані з вимогами професійної діяльності; суб’єктивні, чи особистісні, внутрішні чинники. Виділено форми професійної ідентичності. The need for a scientific approach to the problem of professional growth, the formation of the professional identity of future specialists in nursing is exacerbated by the lack of characteristics characteristics and structure of the investigated quality, the ways and conditions of its formation, teaching and methodological support for this process. The search for effective ways to ensure the professional growth of future junior nursing specialists in the educational environment of a medical college is becoming relevant. It is revealed that distinguish three types of identity: psychophysiological, characterized by the unity of physiological and mental processes and structure of the organism; social - system of properties of a social individual, a member of a certain society, group; personal (His-identity) - the unity of life, goals, motives, values of life, sense of life, personal guidance. Professional identity is a compulsory component of professionalism of a future specialist and one of the conditions for its formation. In professional identity, two aspects are distinguished: 1) awareness of a representative of a particular profession and professional community; 2) consider it as the result of processes of professional self-determination, personalization and self-organization. The main influence on the formation of professional identity are the following distinguished groups of factors: objective or external, factors related to the requirements of professional activity; subjective, or personal, internal factors. The forms of professional identity have been distinguished.
Keywords: професійна ідентичність; майбутні фахівці; молодші спеціалісти сестринської справи; формування професійної ідентичності